2012
DOI: 10.4103/2231-0746.95316
|View full text |Cite
|
Sign up to set email alerts
|

Secondary alveolar bone grafting: Radiographic and clinical evaluation

Abstract: Introduction:Secondary bone grafting of maxilla and residual alveolar clefts at the stage of transitional dentition was first introduced by Boyne and Sands. The aim of this prospective case control study was to clinically and radiologically evaluate the success rate of anterior iliac crest graft in primary alveolar cleft.Methods and Material:In this study we evaluated 10 patients who underwent secondary alveolar bone grafting for various types of cleft palate with autologous iliac crest graft. Type of septum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The frequency of canines impaction in patients with CL/P is determined in the literature as between 0% and 58% [3,[16][17][18][19][20]. Lower frequency of impaction was observed in the groups above 50 persons (0-35%), while the results up to 58% were obtained in the groups with less than 50 patients [21][22][23][24]. It may indicate the higher success of specialist care in multidisciplinary centers.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of canines impaction in patients with CL/P is determined in the literature as between 0% and 58% [3,[16][17][18][19][20]. Lower frequency of impaction was observed in the groups above 50 persons (0-35%), while the results up to 58% were obtained in the groups with less than 50 patients [21][22][23][24]. It may indicate the higher success of specialist care in multidisciplinary centers.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Schultze-Mosgau et al 42 reported a 86% success rate and for the Kawakami et al's 43 study, the success rate of bone graft was reported to be 59% 1 year after surgery. The Kawakami et al's study showed a lower rate of bone graft success than similar studies like the study by Sharma et al, 37 which evaluated the secondary alveolar bone grafting radiographically and clinically. In this study, 10 patients who underwent secondary alveolar bone grafting for different types of cleft palate treated with autologous cranial graft were evaluated.…”
Section: Discussionmentioning
confidence: 88%
“…Many studies have been performed to evaluate the success rate of alveolar bone grafting in patients with cleft lip and palate based on clinical or radiographical scales, reporting mixed results 12,32–38 . However, only few studies have investigated the long-term stability of alveolar bone grafts 34,39 .…”
Section: Evaluation Of Alveolar Bone Graft Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Success or failure of bone grafting has been reported in relation to case number, clinical outcomes, contributing factors, and other domains (Amanat and Langdon, 1991; Frank, 2006; Lilja, 2009). Factors such as age, gender, stage of tooth eruption, cleft side, and cleft size or volume are variables shown to be related to success or failure of SABG (Enemark et al, 1988; Newlands, 2000; Dayashankara Rao et al, 2012; Santiago et al, 2014).…”
Section: Introductionmentioning
confidence: 99%